An investigation of the effect of flow obstructions on critical heat flux, pressure drop and heat transfer. - Vaitekunas, David A. (University of Ottawa (Canada), 2000)
A series of single-phase and two-phase flow experiments were conducted to investigate the effect of flow obstructions on heat transfer, pressure drop, and critical heat flux inside an 8 mm tube. A novel technique of positioning flow obstructions using an external magnetic ring was used to vary the type, spacing, and number of obstacles. Experiments on a single 18%-area and 30%-area ring in liquid Freon-134a show a maximum increase in heat transfer of 10% to 60% at the flow obstacle, and an exponential decay in relative enhancement over 5 to 10 diameters downstream. The associated pressure drop for the 18% ring and 30% ring show a head loss coefficient of 0.12 and 0.26, respectively. A total of 755 CHF data points were obtained for both 30% rings and 3 x 6% area square blockages in Freon-134a and Freon-22. Relative increases of 60% to 100% were obtained in CHF for the same local quality, and 20% to 50% for the same inlet temperature. The results show an exponential rise in CHF with decreased spacing from the exit. There was no accumulative effect (at the exit) when more than 1 obstacle was used to increase CHF, and no decrease in nominal CHF was observed. Analytical models of dryout in annular flow were implemented using an object-oriented framework to simulate the effect of various flow enhancement mechanisms on CHF. Numerous reference tube models were assessed for use in enhancement model analysis. Detailed analysis of liquid film stripping, droplet impingement, and mass transfer enhancement using the models of Whalley et al. (1974), and Hewitt and Govan (1990) show that droplet impingement and mass transfer enhancement are the most likely causes of increased CHF. A 10% to 30% run-off of the entrained liquid impinging on the flow obstruction surface is enough to produce a maximum increase of 20% to 50% in predicted CHF for the same inlet temperature. Subsequently, increases in mass transfer up to 150% to 180% over 30 to 50 diameters are necessary to produce the same CHF enhancement. A different set of flow enhancement parameters were required for each inlet condition, given the complex nature of flow around the obstacle, current limitations in the reference models, and the analytical equivalency between both droplet impingement and mass transfer enhancement. Several recommendations are made for further research in the areas of reference tube modeling, flow visualization, obstacle modeling, and object-oriented simulation.
Keywords: Engineering, Mechanical.